1978
DOI: 10.1128/iai.19.2.481-485.1978
|View full text |Cite
|
Sign up to set email alerts
|

Chicken embryo model for type III group B beta-hemolytic streptococcal septicemia

Abstract: A lethal septicemia was induced in 11-and 12-day-old chicken embryos with intravenous inoculation of relatively small numbers of a clinical isolate (GBBHS-Ill-Bell) or a reference strain (GBBHS-III-D136-C) of group B beta-hemolytic streptococci (GBBHS). GBBHS-III-Bell was more virulent than GBBHS-III-D136-C, and 11-day-old chicken embryos were more susceptible than 12-day-old chicken embryos. Type-specific rabbit antisera protected the embryos from bacterial challenge, and this protective effect was absorbed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…To 100 ~tl of type Ia antiserum, 10 #g of Ib antigen was added and after incubation at 4°C overnight, the sample was centrifuged a n d placed in well [1]. Similarly, the same a m o u n t of Ib antigen was added to type III antiserum a n d placed in well [2] as a control. It can be seen that in the case of the type III serum the Ib antigen remained detectable, whereas it was completely b o u n d by the Ia serum.…”
Section: Characterization Of Iabc Component It Was First Reported Bymentioning
confidence: 99%
“…To 100 ~tl of type Ia antiserum, 10 #g of Ib antigen was added and after incubation at 4°C overnight, the sample was centrifuged a n d placed in well [1]. Similarly, the same a m o u n t of Ib antigen was added to type III antiserum a n d placed in well [2] as a control. It can be seen that in the case of the type III serum the Ib antigen remained detectable, whereas it was completely b o u n d by the Ia serum.…”
Section: Characterization Of Iabc Component It Was First Reported Bymentioning
confidence: 99%
“…Studies from several laboratories have es-tablished that antibody is important in GBS immunity (4)(5)(6)(7). Antibody to GBS has been shown to provide protection in several animal models including suckling rats (81, chick embryos (9), and mice (4,10) given lethal challenge of GBS. Furthermore, in vitro studies have demonstrated that efficient phagocytosis and killing of GBS by neutrophils or monocytes requires opsonic antibody (5)(6)(7).…”
mentioning
confidence: 99%
“…Recently, the chicken embryo was reported to be an excellent animal model for studying the virulence of microorganisms pathogenic for humans such as Neisseria gonorrhoeae [8], Neisseria meningitidis [14], Listeria spp. [6] and group B streptococci [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dose-lethality curves were established by i.v. inoculation (usually through the chorioallantoic vein) of 12-day-old chicken embryos with increasing numbers of group A streptococci in 0.1 ml Todd Hewitt broth by the method of Tiefenberg et al [32]. The cfu's were determined by using a counting chamber, whereby 3 cells within a chain were counted as one cfu.…”
Section: Chicken Embryo Assaymentioning
confidence: 99%